BioCode: Third time lucky? - Flann, Christina (Zootaxa, 2011)
Fifteen year ago a draft BioCode was presented to the taxonomic community (Greuter et al. 1996). There is now a new version, published in Taxon (Greuter et al. 2011) and available online on the International Committee on Biological Nomenclature website as well as that of the International Commision for Zoological Nomenclature. Has the BioCode matured since it was last put forward? Was it ahead of its time in the 1990s, particularly in relation to the possibilities of electronic registration? Is it the future yet? As a taxonomist with an active interest in (botanical) nomenclature, I was still a student when this arose the last time and have referred to the literature to see what happened then. Interestingly it turns out that it wasn’t the first time a biocode equivalent was suggested. Minelli (2008) discusses the suggestions drafted by a commission appointed on request of the zoologist Carlo Luciano Bonaparte in regard to the so-called Strickland Code (Strickland et al. 1842), these ideas, like the 1996 BioCode, were not accepted by the taxonomic community. Perhaps third time lucky?